Some aspects of recidivism in criminal law and criminology - Mijalčić, Jelena (Glasnik Advokatske komore Vojvodine, 2023)
In this article, the author analysis some criminal law and criminological aspects of recidivism. The factors which most often lead to phenomenon of recidivism are analysed, as well as different types of personality of recidivists. The author analyses the most important types of recidivism, as well as the criminal law significance of each of the mentioned types of recidivism. Based on this presentation, the author presents some ideas about reducing recidvism on the lowest level in one social system.